Opportunities and contraints in the restoration of riparian ecosystems invaded by alien trees : insights from the Western Cape, South Africa - Ruwanza, Sheunesu (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.